Analysis of Social Philosophy and Nutritional Knowledge in the Practice of Moci Tradition in Tegal Community - Sefia Citra Adittya; Harto Wicaksono (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
In the Tegal region of Central Java, there is a tradition of drinking “Moci” tea, which has social philosophical values embedded within it. An anthropological perspective, particularly cultural and health anthropology, is used to examine how this tea drinking tradition is interesting to study from a social perspective and in terms of the local knowledge inherent in the daily practices of the community. Therefore, this study aims to examine the social philosophical values in the Moci tradition and Tegalan’s knowledge of the nutritional benefits of teh poci for health. The concept of The Factor of Food Habits is used to frame the researcher's analysis. This study uses qualitative research methods with an ethnographic approach. This research was conducted in the Tegal region from May 2024 to April 2025. Data collection was carried out through observation, interviews, and documentation. There were ten informants involved in this study, consisting of cultural observers, local communities, and nutrition experts. Based on the results of the study, it was found that the Tegalan interprets the Moci tradition as an effective strategy in maintaining solidarity and strengthening egalitarianism in Tegalan. Based on the concept of The Factor of Food Habits, the Tegalan focus on morally dictated changes based on the selection of tea ingredients that are considered good for health, such as the type of sugar used and the influence of certain physical activities that require the consumption of this type of drink.